Bilateral infectious urolithiasis as a risk factor for acute kidney failure in a 3-year-old boy - Karina Madej-Świątkowska; Magdalena Błasiak; Monika Miklaszewska; Andrzej Haliński; Adam Haliński; Katarzyna Zachwieja; Anna Moczulska; Dorota Drożdż (Termedia Publishing House, 2024)
Infectious urolithiasis is a relatively rare form of urolithiasis in children. The predisposing factors in the pediatric population mainly include urinary tract defects and neurogenic bladder. Here we present a case of a 3-year-old boy with staghorn calculi, diagnosed during the diagnostic management for persistent leukocyturia. The boy had a history of recurrent urinary tract infections (rUTIs) caused by Proteus mirabilis and Klebsiella pneumoniae . Based on laboratory tests and imaging studies, the patient was diagnosed with a dysfunctional right kidney and a significant risk due to a large staghorn calculus to the left kidney. Bilateral ureteroscopic lithotripsy was performed, the deposit from the left kidney was removed via open surgery, and the narrowed sections of the ureters were excised. During the follow-up period, the patient's glomerular filtration rate remained normal. In the case of rUTIs kidney calculi may be diagnosed incidentally as they produce no clear clinical symptoms.